The Impact of COVID-Pandemic and Media on Sustainability and Employee Retention, In Malaysian Industries - Ishaq Ibrahim; Walid Abdullah Al-Suraihi; Al-Hussain Abdullah Al-Suraihi; Kalsom Ali (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd., 2024)
Volume 5, Issue 2, Pages 1-6